Analysis of a MMC-Based 12-MW Direct-Drive Wind Energy Conversion System With Level-Shifted and PS-PWM and NLM Strategies - Andrei O. Almeida; Matheus S. Paulo; Daniel P. Teixeira; Rodolfo Lacerda Valle; Pedro M. Almeida; Pedro Gomes Barbosa (Eletrônica de Potência)
This paper analyzes a 12-MW direct-drive wind energy converter system featuring a 6.6-kV, 132-pole permanent magnet synchronous generator, similar to the Haliade-X 12-MW manufactured by General Electric. The proposed system utilizes a back-to-back modular multilevel converter (B2B-MMC) with four submodules per arm. The research investigates three modulation strategies: nearest level modulation and two variants of multicarrier pulse width modulation that incorporate level-shift and phase-shift techniques. Additionally, it examines the interaction between the generator's low frequency and the design parameters of the MMC. Thus, this paper contributes to the understanding of the effectiveness of the B2B-MMC as a viable solution for direct-drive low-frequency wind generators. Furthermore, it analyzes how the modulation strategy and voltage equalization algorithm impact system performance, especially with the implementation of a subsampling technique. Digital simulations carried out with PSCAD/EMTDC provide a comparative analysis of the three modulation strategies investigated.